Non-human Primate Determinants of Natural Killer Cells in Tissues at Steady-State and During Simian Immunodeficiency Virus Infection - Huot, Nicolas; Rascle, Philippe; Petitdemange, Caroline; Contreras, Vanessa; Palgen, Jean-Louis; Stahl-Hennig, Christiane; Le Grand, Roger; Beignon, Anne-Sophie; Jacquelin, Beatrice; Müller-Trutwin, Michaela (Frontiers in Immunology, 2020)
Natural killer (NK) cells play essential roles in immunity to viruses and tumors. Their function is genetically determined but also modulated by environmental factors. The distribution and functional regulation of these cells vary depending on the tissue. NK cell behavior in lymphoid tissues is so far understudied. Non-human primate (NHP) models are essential for the development of therapies and vaccines against human diseases and access to NHP tissues allows insights into spatial regulations of NK cells. Here, we investigated tissue-specific phenotypes and function of NK cells from NHP species, i.e. cynomolgus macaque (Macaca cynomolgus), African green monkey (Chlorocebus aethiops), rhesus macaque (Macaca mulatta) and baboon (Papio, anubis). By comprehensive multi-dimensional analysis of NK cells from secondary lymphoid organs, intestinal mucosa, liver and blood, we identified tissue- and species-specific patterns of NK cell frequencies, phenotype and function. In addition, we defined tissue-specific characteristics of NK cells during an infection by the simian immunodeficiency virus. Altogether, our results provide a comprehensive anatomic analysis of NK cells in different tissues of primates at steady state and during a viral infection.